2013
DOI: 10.1111/pace.12069
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Lower Limb Compression in the Management of Vasovagal Syncope—Randomized, Crossover Study

Abstract: Compression of the lower limbs is very effective to render the TT negative in patients with a diagnosis of VS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Several nonpharmacologic strategies can be employed to improve venous pooling in the splanchnic, pelvic, and lower extremity circulation (51). Graded compression garments and abdominal binders have improved symptoms of orthostatic intolerance in conditions associated with excessive blood pooling (52,53). The combination of abdominal binders and lower extremity compression stockings is thought to be more effective than lower extremity compression alone due to the disproportionally greater volume in the splanchnic circulation than in the legs (51).…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%
“…Several nonpharmacologic strategies can be employed to improve venous pooling in the splanchnic, pelvic, and lower extremity circulation (51). Graded compression garments and abdominal binders have improved symptoms of orthostatic intolerance in conditions associated with excessive blood pooling (52,53). The combination of abdominal binders and lower extremity compression stockings is thought to be more effective than lower extremity compression alone due to the disproportionally greater volume in the splanchnic circulation than in the legs (51).…”
Section: Nonpharmacologic Interventionsmentioning
confidence: 99%
“…It was demonstrated that the compression garment decreased venous pooling, increased systolic blood pressure, attenuated the reductions in stroke volume and cardiac output (Stenger et al 2010), and prevented tachycardia with standing after spaceflight (Stenger et al 2014; Stenger et al 2013). The compression garment was also found to be effective in the prevention of orthostatic intolerance in orthostatically intolerant athletes (Privett et al 2010), and to render the tilt-test negative in patients with a clinical diagnosis of recurrent syncope (Dos Santos et al 2013).…”
Section: Reduction In Venous Poolingmentioning
confidence: 99%
“…Excessive venous pooling is thought to occur in POTS, particularly in the lower extremities and splanchnic venous beds 37 . Compression garments have been used effectively as a countermeasure to prevent excessive venous pooling in the lower extremities of patients with POTS 38,39 . Given the relative volume of the abdominal cavity compared with the lower extremities, compression garments are recommended to extend to the lower abdomen.…”
Section: General Management Of Potsmentioning
confidence: 99%